Mastitis Mikotik Akibat Terinfeksi Candida spp dan Trichosporon spp pada Peternakan Sapi Perah di Bogor, Bandung, dan Jakarta (MYCOTIC MASTITIS CAUSED BY CANDIDA SPP AND TRICHOSPORON SPP ON DAIRY FARM IN BOGOR, BANDUNG, AND JAKARTA) - Ahmad, Riza Zainuddin; Gholib, Djaenudin (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
Mycotic mastitis is a disease affecting dairy cows and the causative agent is fungi of yeast, and alsomolds, but the disease is dominantly caused by yeast. In Indonesia reported of the disease is very rare.Generally, the mycotic mastitis is chronic causing great economic losses. This study aim was to show thatthere are still cases of mycotic mastitis in dairy cows in the area of Bandung, Bogor and Jakarta. Isolationand identification of fungi that caused mycotic mastitis were performed from the positive milk samplesteseted with California Mastitis Test (CMT). Of the 184 positive samples mastitis tested with CMT, 71samples mycotic mastitis were obtained, The 71 samples consisted of 13 molds and 84 yeasts based onthe isolates findings. Consecutive areas where commonly found mycotic mastitis were Bogor (50%);Bandung (38%); and Jakarta (27%). The number of positive samples in mycotic mastitis caused by moldinfection findings obtained less than yeasts. The yeast of Trichosporon spp found 34 isolates which washigher than Candida spp at 26 isolates. The existence of this yeast contamination was associated with thehygiene of the cage and the dairy cows. Control needs to be done to reduce the cases of mycotic mastitis.
Keywords: mycotic mastitis; yeast; dairy cows; California Mastitis Test (CMT)